Investigating the culturable atmospheric fungal and bacterial microbiome in West Texas: implication of dust storms and origins of the air parcels. Issue 1 (15th December 2020) - Elmassry, Moamen M; Ray, Nandini; Sorge, Sara; Webster, Jennifer; Merry, Kyle; Caserio, Angelica; Vecellio, Daniel J; Kruczek, Cassandra; Dowd, Scot; Ardon-Dryer, Karin; Vanos, Jennifer; San Francisco, Michael J
ABSTRACT: Individuals often experience ailments such as allergies, asthma and respiratory tract infections throughout the year. Weather reports often include estimations of common allergens that can affect these individuals. To describe the local 'atmospheric microbiome' in Lubbock, Texas, USA, we examined the culturable fungal and bacterial microbiome present in the air on calm and dust storm days using internal transcribed spacer (ITS)-1 and 16S rRNA amplicon sequencing, respectively. While some types of airborne fungi were frequently present throughout the year, distinct differences were also observed between calm and dust storm days. We also observed the influence of the origin of air parcels and wind elevation of the air trajectory. The most abundant genera of fungi identified during the study period were Cryptococcus, Aureobasidium, Alternaria, Cladosporium and Filobasidium . This observation was not surprising considering the agricultural intensive environment of West Texas. Interestingly, Cladosporium, a common allergenic mold, was increased during days with dust storm events. The predominant bacterial genera observed were Bacillus, Pseudomonas, Psychrobacter, Massilia and Exiguobacterium . The relative abundance of the psychrophiles, Psychrobacter and Exiguobacterium, was surprising, given the semi-aridity of West Texas. Coupling our observations with back trajectories of the wind (Hybrid Single-Particle Lagrangian Integrated Trajectory models) demonstrated that dust storms, regional anthropogenic activity and origin of air parcels are important influences on the diversity and temporal presence of the atmospheric microbiome. Abstract : Dust storms impact the atmospheric microbiome; for example they increase the abundance of Cladosporium, an allergenic fungus that may affect the health of susceptible individuals.